2021
DOI: 10.3390/vetsci8090186
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Cruciate Ligament Rupture in Dogs: Review on Biomechanics, Etiopathogenetic Factors and Rehabilitation

Abstract: Cranial cruciate ligament (CrCL) rupture is one of the most common orthopaedic conditions in veterinary medicine. CrCL plays a fundamental role in the stability and biomechanics of the femoral-tibio-patellar joint, and its incorrect functionality severely impacts on the quality of life of patients. In dogs, the structural weakening of this joint due to the progressive degeneration of the ligament is the most accredited etiopathogenetic hypothesis in relation to the dog signalment (breed, sex and age) and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 178 publications
(281 reference statements)
1
12
0
Order By: Relevance
“…A recent review of etiopathogenetic factors reported that the main predisposing factors for rupture of the CrCL include age between 2 and 10 years, having been neutered or spayed, and being large and/or overweight. 30 Notably, the population in this study was at little risk of having these predisposing factors.…”
Section: Discussionmentioning
confidence: 72%
“…A recent review of etiopathogenetic factors reported that the main predisposing factors for rupture of the CrCL include age between 2 and 10 years, having been neutered or spayed, and being large and/or overweight. 30 Notably, the population in this study was at little risk of having these predisposing factors.…”
Section: Discussionmentioning
confidence: 72%
“…A positive outcome for orthopaedic disorders is dependent on optimal return to normal muscle function. One of the most common orthopaedic disorders causing lameness in dogs is cranial cruciate ligament disease (CCLD) (1)(2)(3)(4)(5). In CCLD, the function of the skeletal muscles is particularly challenged, as the normal stabilising synergism between the large muscles around the canine stifle joint and the cruciate ligaments is disrupted (1).…”
Section: Introduction Rationalementioning
confidence: 99%
“…Patellar alta may be among the pathologies of medial patellar luxation ( Mostafa et al , 2008 ). In addition, medial patellar luxation could be a factor in CCLD, especially in small dogs ( Campbell et al , 2010 ; Spinella et al , 2021 ). Accordingly, there are scattered cases of concomitant CCLD and medial patellar luxation, and patellar alta may occur among these cases.…”
Section: Discussionmentioning
confidence: 99%